МОНГОЛ УЛСЫН ЕРӨНХИЙЛӨГЧИЙН СОНГУУЛИЙН СУДАЛГААНЫ ТАЙЛАН - Ц.Ганболд (Politology, 2023)
The aim of the survey was to define the starting condition of Presidential election of Mongolia in 2013. The survey data has been collected through quantitative research basic method of questionnaire, and processed by social analysis appropriate programs as well as CS pro for survey data base and SPSS for processing and statistic analysis. Data collection locations’ has been determined by the subscriber. 18 years’ old and above electorates’ have been survey respondents. Total selection was 1200 electorates. The feasible average of 1000-1500 electorates’ for nation-wide survey has already been proved through last 10 years’ research results in Mongolia. Moreover, in America, it has been defined that selection sampling of 957 respondents for total plurality of 1500.000 has 5 % for maximum percentage of failure and 95 % for quotient level.